Web-based reference manager application of Dublin core in content analysis - Hernandez, Allan; Senal, Dennis David S. (2004)
One of the most pressing demands of organizations is the management of its assets in context of information exchange and allocation. The need for effective management, retrieval and distribution of relevant information both internally and externally has never been greater. Information in the form of document files, media, reports, user profiles, surveys, figures and a myriad of other sources flows in and out of the organization on a regular basis.